The Study of Chromosomal Structure in Mystus pelusius (Solander in Russell,1794) Fish - AL-Khayat, Asmaa S.I.; Sahan, Heba H. R. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
The present study was done to identify the karyotype of Mystus pelusius fish , which is the only representative of the family Bagridae in Iraq, they have been caught from Tigris river in AL-Kraat area of Baghdad city, the results show that the diploid chromosome number was 2n=32 and the males chromosomal types included 2n=(6m+13sm+7st+6t)and fundamental number FN=51, in females chromosomal types included 2n=(6m+12sm+8st+6t)with FN=50,also it observed that the first submetacentric pair was the largest within the biarmed chromosomes .The results revealed that the male heterogamety and the female homogamety , accordingly it follows the sex determination system (XX / XY) , as the (X) chromosome represented by medium sized submetacentric (sm)chromosome and (Y)chromosome by small sized subtelocentric (st) chromosome.